TECHNOLOGICAL FUNDAMENTALS OF IMPROVING THE DEVICE FOR CRUSHING COATS - G’ulomjonovna, Yoqubjonova Yoqutxon; Xoshimjono’gli, Yuldashev Shakhboz (The journal of contemporary issues in business and government, 2021)
Corn is not only a feed product needed for livestock and poultry, but also the most important food product for humans. Today, in all categories of farms of the republic it is planned to plant corn as the main crop on 138,500 hectares for grain, from which 1210,900 tons of grain will be harvested. However, harvesting harvested corn for grain is one of the most difficult and arduous processes, with quality harvesting at an early stage without destroying the ripe crop in a mechanized manner.